2018
DOI: 10.24093/awej/vol9no4.7
|View full text |Cite
|
Sign up to set email alerts
|

WhatsApp: An Online Platform for University-Level English Language Education

Abstract: Technology has developed immensely and its role in the aspects of learning a language has grown bigger and bigger. Among the university level students, WhatsApp at present is getting into the frontline as one of the most widespread online social networking platforms concerning to language learning. The research work undertaken tries to understand if university level students consider WhatsApp as a significant learning platform that can develop and support their language learning skills. Moreover, , the researc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 0 publications
4
16
0
Order By: Relevance
“…This indicated that participants were aware of the efficiencies and affordances of WhatsApp for learning English idioms. This finding corresponds with those of prior studies (Alghamdy, 2019;Alqahtani et al, 2018;Alshammari et al, 2017;Bensalem, 2018;Çam & Can, 2019;Çetinkaya & Sütçü, 2018) that indicated that students have positive perception about the use of WhatsApp in language learning.…”
Section: Discussionsupporting
confidence: 91%
“…This indicated that participants were aware of the efficiencies and affordances of WhatsApp for learning English idioms. This finding corresponds with those of prior studies (Alghamdy, 2019;Alqahtani et al, 2018;Alshammari et al, 2017;Bensalem, 2018;Çam & Can, 2019;Çetinkaya & Sütçü, 2018) that indicated that students have positive perception about the use of WhatsApp in language learning.…”
Section: Discussionsupporting
confidence: 91%
“…This indicated that participants were aware of the efficiencies and affordances of WhatsApp for learning English idioms. This finding corresponds with those of prior studies (Alghamdy, 2019;Alqahtani et al, 2018;Alshammari et al, 2017;Bensalem, 2018;Çam & Can, 2019;Çetinkaya & Sütçü, 2018) that indicated that students have positive perception about the use of WhatsApp in language learning. The findings showed that, of the five given constructs, ease of use was perceived as the most important.…”
Section: Discussionsupporting
confidence: 91%
“…• The use of WhatsApp has been successful during the confinement period as a support to complete the modules and meet learning objectives. WhatsApp already formed part of the students' e-routine which concurs with the findings of [2]. The features of instant messaging and traceability helped bond a cordial collaborative community of learners.…”
Section: Discussionsupporting
confidence: 75%
“…Alqahtani et al [2] advanced that the extensive use smartphones by university students in many parts of the world shows that smartphones have become an important element of their e-routines. The smart phone was chosen as instrument.…”
Section: The Smart Phonementioning
confidence: 99%